Analisis Sektor Unggulan dan Strategi Pengembangan Ekonomi Wilayah di Kecamatan Polombangkeng Selatan - Irsyadi Siradjuddin (Jurnal Ekonomi-Qu, 2025)
This study analyzes the economic potential and commodity production in Polongbangkeng Selatan District, Takalar Regency, South Sulawesi. The area covers 88.07 km² with low to moderate topography, has two main soil types (inceptisol and ultisol), and annual rainfall of 2,500–3,000 mm. The population growth rate of 1.49% per year with the majority of the population in the productive age (66%), supports the potential for economic development. The analysis results indicate that superior commodities such as rice, corn, and cassava, while commodities such as soybeans and mung beans have less potential. Based on Shift Share and Klassen Typology analysis, rice shows progressive growth and is a leading sector, while corn and cassava are included in the mainstay and prospective sectors. The agricultural sector dominates the regional economic contribution, followed by rattan handicrafts which show development potential with a profit margin of 28.57%. Development strategies include focusing on increasing the productivity of superior commodities, product diversification, digital-based marketing, and integration aspects that want to be implemented in production practices. The results of this study provide a strategic basis for optimizing the region's economic potential.